RANCANG BANGUN APLIKASI BUKU INDUK SISWA BERBASIS WEB PADA SMA BARUNAWATI SURABAYA - Amala, Khamim Ahsanu; Arifin, Mochammad; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
SMA Barunawati Surabaya is a senior secondary or vocational education institution that was founded in 1983 and is located on Jalan Raya Perak Barat 173 Surabaya. At SMA Barunawati there are 2 (two) Class Departments, namely the Natural Science Class (IPA) and the Social Science Class (IPS), with details of each level, among others, Class X (Ten) with a total of 8 (Eight) classes with details of IPA Class as many as 4 (Four) Classes and Social Class as many as 4 Classes, Eleven (XI) Classes as many as 7 (Seven) Classes with 4 (four) Classes and Social Sciences Class as many as 3 (Three) Classes, XII Class (Twelve) as many as 6 (six) classes with details of 3 (three) classes of science class and 3 (three) classes of social science. In admitting new students, SMA Barunawati will record student data in the Buku Induk.To solve this problem, Buku Induk application system is needed. This system will be made web-based which is easier to access so that the school can use the application as needed. The results of this study are in the form of BBuku Induk application system for SMA Barunawati Surabaya students that has been tested so that the Administration section can be helped in carrying out the activities of the main book process. In addition, this application is also a place to back up student data, as well as generate student masterbook data dynamically and where it can make changing student data easier.